Artefacts, found objects and early games. A cultural ecological perspective on proto-chess pieces. (2nd January 2020) - Dillon, Patrick
ABSTRACT: The game of chess and its immediate precursors have a history of over 2, 000 years. But what of the prehistory of the game and the pieces used? The hypothesis presented in this article is that the development of the pieces that are now associated with chess is part of a cultural ecological continuum of gaming materials through stones and other naturally occurring materials with simple shapes, stones shaped and embellished by human hands, naturally occurring stones with human or animal likenesses, figurines made from stone, clay, wood and other materials, and proto-chess pieces. It is suggested that comparative analysis of artefact assemblages, taking account of context, associated objects, spatial distributions and usage histories, may reveal patterns and connections that enable a more refined understanding of how the symbolism and iconography of chess developed and how they are reflected in the selection of gaming materials and the emergence of proto-chess pieces.